Point of Sale Framework-Based Code Igniter and Model View Controller Using Lighthouse Testing - Syaifudin, Muhammad; Fauziah, Fauziah; Rahman, Ben (Information Technology and Science (ITScience), 2021)
The success of companies engaged in the field of distributors is not only from good and smart human resources, but how ready the company's way to provide tools or programs supporting the work of employees. Some of the problems are the administration system between the company's internal divisions, so there are restrictions on the processing of input data, processes, outputs that are still manual. Web Application is made to facilitate employees to conduct administrative activities with the access role of each user admin division, for example inventory data, creation of sales invoices, road letters, procurement forms and bookkeeping. In addition, The Web View application is already responsive in this sense can adjust the device PC / Tablet / Mobile, then for visualization of data calculation already using cart / data graphics in real time, and there is also a feature preview, download and print JPEG, PNG, PDF, Barcode and QR code. Web Testing This application with black box method and shows it is running well and no error method, so it can be declared passed. Web Creation This application involves the LTE 2.0 Admin Template with bootstrap CSS, for programmer frameworks using MVC model view controllers that exist in the Code Igniter 3.0 framework so that it is faster and easier to implement or developed in other field companies or in the manufacturing industry. Tests using lighthouse for perform by 94% showed that the application designed to have a good performance for display results, and its access value of 60%, indicating that the process related to responsiveness between users is appropriate both using PC / Tablet / Mobile